Cassatella, Claudia; Peano, Attilia (eds.) (2011): Landscape indicators: Assessing and monitoring landscape quality - Llausàs Pascual, Albert (Documents d’Anàlisi Geogràfica, 2012)
Cassatella, Claudia; Peano, Attilia (eds.) (2011) Landscape indicators: Assessing and monitoring landscape quality Dordrecht: Springer, 222 pàgines ISBN: 978-94-007-0365-0